Surgical Management of Childhood Glaucoma Clinical Considerations and Techniques (Springer International Publishing, 2018)
This comprehensive guide thoroughly covers the characteristics and presentations of childhood glaucoma, as well as all surgical options for treatment. Surgical Management of Childhood Glaucoma: Clinical Considerations and Techniques addresses a variety of surgical methods, ranging from angle surgery with recent modifications to cyclodestruction, reviewing each option's particular set of advantages and disadvantages, and features illustrations and instructional videos of these techniques. Later chapters consider best-practices to providing surgery in developing countries, surgical considerations for patients with corneal opacities and cataracts, and the impact of glaucoma upon quality of life of pediatric patients. Written by leaders in the field of ophthalmology, this book offers readers an exceptional resource on the evaluation and surgical management of childhood glaucoma.